(untitled) (Al-Aasar, 2025)
Long standing geopolitical tensions were rekindled after the Pahalgam terrorist incident in 2025, which prompted a surge of nationalist rhetoric on both sides of India- Pakistan conflict. This qualitative study dives into how Indian Prime Minister Narendra Modi and Pakistani Prime Minister Shehbaz Sharif crafted their messages with metaphors following the ceasefire. It leans on Conceptual Metaphor Theory (CMT) to pinpoint the significant metaphors each leader used in their speeches. The results of the study depicted that Modi often reached for mythological references and military language to back up India’s stance. On the flip side, Sharif leaned more towards ideas of moral courage and peace, painting Pakistan as a nation standing up against injustice and holding onto its moral integrity. The study also reveals the power of language in shaping narratives, especially during tough times like war. Metaphors can really stir up national sentiment, cast the adversary in a bad light, and even legitimize military actions. This research sheds light on how political metaphors keep fueling ideological divides in South Asia.